Penerapan Asas Cabotage dan Kontrol Negara terhadap Investasi Asing dalam Pengangkutan Laut di Indonesia - Ghazi Luthfi (Jurnal Hukum Lex Generalis, 2025)
In the field of maritime transportation, there is a generally accepted principle worldwide known as the Cabotage principle. This principle stipulates that domestic maritime transport activities must be conducted by local shipping companies using national flagged vessels with local crew members. Cabotage Principle implementation prevents foreign shipping legal entities from conducting business activities to serve maritime transport between ports in the the territory of Indonesia. Consequently, to engage in such business activities, foreign shipping companies must establish subsidiaries in Indonesia. However, according to investment regulations in Indonesia, foreign investors are limited to a maximum capital ownership of 49% to establish a shipping company. This paper will examine Cabotage principle implementation, which necessitates foreign investment in Indonesia for domestic maritime transport, with the investment being limited to a max of 49%. This will be analyzed in the relation to application of Control by the Host State and the principles of protection in the Foreign Investment Agreement agreed upon by the Indonesian Government with other countries.